Levels of anxiety: practice vs. competition in NCAA Division I North American football players - Allie, J.; Larson, A.; DeBeliso, M. (International Journal of Sports Science, 2018)
High levels of cognitive and somatic anxiety may be detrimental to sport performance as well as increase risk of sport-related injury. It is important to identify situations that are likely to cause high levels of anxiety so appropriate self-regulation and anxiety management techniques can be employed. PURPOSE: The purpose of this study was to 1) determine if anxiety level differs between NCAA Division 1 North American football players based on position played and 2) determine intra-individual and inter-position differences in anxiety level prior to a scrimmage versus a practice scenario. METHODS: NCAA Division I North American football players (n=36) completed a modified Sport Competition Anxiety Test (SCAT-A) survey prior to a practice session and again prior to a scrimmage. RESULTS: The results of the SCAT-A were first sorted by anxiety category (low, average, and high) and subsequently sorted on position: offensive player (OFF)/defensive player (DEF), as well as high contact (HC)/low Contact (LC). A Fisher`s exact statistical test was used to make 6 different comparisons based on position and scenario. Anxiety categories were compared between OFF and DEF for the practice session as well as the scrimmage. Likewise, anxiety categories were compared between HC and LC for the practice session and the scrimmage. Finally, anxiety categories were compared within groups for OFF and DEF between the practice session and the scrimmage. No statistical differences in anxiety categories were found between positions or between the practice and the scrimmage (p>0.05). CONCLUSIONS: Within the parameters of this study, contrary to the research hypothesis, anxiety levels do not appear to change based on position or the competitive scenario.